The SAGE handbook of globalization - Steger, Manfred B. 1961-; Battersby, Paul 1961-; Siracusa, Joseph M. 1944- (SAGE, 2014)
Global studies is a fresh and dynamic discipline area that promises to reinvigorate undergraduate and postgraduate education in the social sciences and humanities. This Handbook allows for extended treatment of critical issues that are of major interest to researchers and students in this emerging field, encompassing sociology, anthropology, history, media and cultural studies, economics and governance, environmental sustainability, international law and criminal justice